Assessment of R-438A as a retrofit refrigerant for R-22 in direct expansion water chiller. (February 2015) - Elgendy, E.; Hassanain, M.; Fatouh, M.
Abstract: The present work aims to evaluate the performance characteristics of a vapor compression refrigeration system using R-438A as a retrofit refrigerant for R-22. In order to achieve this objective, a test facility is developed and experiments are performed over a wide range of chilled water inlet temperature (11:20 °C), condenser water inlet temperature (25:35 °C) and condenser water mass flow rate (363:543 kg h −1 ). Results showed that as the chilled water inlet temperature changes from 11.5 to 20.5 °C, system COP increases from 1.78 to 2.07 at constant condenser water inlet temperature of 25.5 °C. Cooling capacity and COP of the system using R-438A are lower than R-22 by 11% and 12.5%, respectively. However, compressor discharge temperature using R-438A is slightly lower than R-22 which confirms that R-438A can be used as a retrofit refrigerant for R-22 to complete the remaining life time of the existing plants. Highlights: Performance of R-438A refrigerant in DX water chiller is experimentally investigated. R-438A has the same pressure levels, lower discharge temperature as compared with R-22. R-438A requires minor adjustments to retrofit in the R-22 DX water chiller. Cooling capacity and coefficient of performance is decreased by 11% and 12.5% using R-438A.